Individualizing Utopia: Individualist Pursuits in a Collective Cohousing Community. (October 2016) - Sullivan, Esther
Through a fourteen-month ethnography of a cohousing community, this study explores how community members reexamine and redefine their collectivist values in an attempt to develop their ideal community. Cohousers voice distaste for the isolation of contemporary U.S. residential arrangements and collaboratively plan neighborhoods that promote common space, increased social interaction, and collective decision making. Despite these organizing principles, I find that the conditions for social cohesion in one cohousing community are based primarily on concessions to autonomy and privacy, and emphasis on personal rewards for individual members. I demonstrate how this occurs in "Sunrise Place" as the group's members (1) develop spatial arrangements that emphasize domestic privacy and (2) practice consensus decision making in ways that prioritize individual self-reflection over group debate. I show that cohousers' apparently contradictory focus on the individual actually aids their collectivist agenda by buttressing members' investment in the project during a prolonged development process; however, the community they develop is physically and spatially insulated, reproducing aspects of domestic privatism they seek to subvert.